(3efThQ dCHi GdNjQ SdGegs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje cJHJ GWGd Gddg HbGA CNj GdTjN GHh GdNjQ SdGeI hGOGe JCjjOg hMQGSJg s
(3BNQgG (B:s
(3heYLd NRjge Ydi eG GMJbHhg hebQH aVjMJge bHd hQhO GLGdge JeJ hGdMeO dehdGfG hMOg hGdTcQ GdbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis